2016
DOI: 10.4238/gmr.15026998
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor (TLR)-2/4 expression in retinal ganglion cells in a high-glucose environment and its implications

Abstract: ABSTRACT. Diabetic retinopathy (DR), a major complication of diabetes mellitus, is the leading cause of adult blindness. The Toll-like receptor (TLR) family is believed to be involved in the pathogenesis and progression of DR. Here, we investigated the expression profiles of TLR-2 and TLR-4 in retinal ganglion cells (RGCs), in an attempt to elucidate the role of these molecules in the etiology of DR. In vitro cultured RGCs were divided into control and high-glucose groups. The mRNA and protein levels of TLR-2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
(17 reference statements)
0
16
0
Order By: Relevance
“…The expression of TLR-2 was upregulated in obese/T2DM patients and was associated with inflammatory response as assessed by increased serum levels of IL-18 (Mohamed et al, 2016). A high-glucose level could also induce TLR-2 and TLR-4 expression in retinal ganglion cells via increase in the secretion of pro-inflammatory factors in diabetic retinopathy (Zhao et al, 2016).…”
Section: Obesity and Type 2 Diabetes Mellitus (T2dm)mentioning
confidence: 96%
“…The expression of TLR-2 was upregulated in obese/T2DM patients and was associated with inflammatory response as assessed by increased serum levels of IL-18 (Mohamed et al, 2016). A high-glucose level could also induce TLR-2 and TLR-4 expression in retinal ganglion cells via increase in the secretion of pro-inflammatory factors in diabetic retinopathy (Zhao et al, 2016).…”
Section: Obesity and Type 2 Diabetes Mellitus (T2dm)mentioning
confidence: 96%
“…The activation of microglia is determined by extracellular signals, including neuronal damage, chronic neurodegeneration, dying cells, extracellular liposaccharides and nucleic acids, which are recognized by a broad range of receptors [ 82 , 96 ], such as toll-like receptors (TLR) and receptors of advanced glycation end products. These enable microglia to detect pathogens via signaling of the pro-inflammatory nuclear transcription factor NFκB [ 97 ]. Translocation of NFκB is followed by production of cytokines and other inflammatory mediators.…”
Section: Microgliamentioning
confidence: 99%
“…Decreasing oxidation stress, e.g., via VP10/39 would be a promising therapeutic for DR [ 130 ]. The activation of NFκB leads to further production of cytokines and other inflammatory mediators [ 97 ]. NFκB was increased in activated microglia after hypoxia induction and was required for retinal angiogenesis [ 65 ].…”
Section: Microgliamentioning
confidence: 99%
“…In addition, TLR-2 and -4 signaling pathways appear to be the main triggers of these inflammatory responses. Recent in vitro studies have shown that high concentrations of glucose significantly increase TLR-2 and TLR-4 mRNA and protein expression in human microvascular ECs, as well as the activation of NF-κB p65, the expression of inflammatory markers such as interleukin (IL)-8, IL-1β, TNF-α, MCP-1, and vascular cell adhesion molecule (VCAM)-1 and intercellular adhesion molecule (ICAM)-1 [64,65]. All these events were reversed by TLR-4 or TLR-2 inhibition, or dual inhibition of these pathways by TLR4/2 inhibitory peptide.…”
Section: The Tlr-2 and -4 Inflammatory Signaling Pathwaysmentioning
confidence: 99%